2010
DOI: 10.1038/jhh.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Increased nighttime blood pressure or nondipping profile for prediction of cardiovascular outcomes

Abstract: At present, clinic blood pressure (BP) evaluation is being increasingly complemented by ambulatory BP measurements for the evaluation of haemodynamic patterns during daily activities and sleep. Nondipping pattern, a measure of decreased attenuation of nighttime over daytime BP, has been correlated with enhanced target organ damage and adverse cardiovascular (CV) outcomes in different clinical settings beyond pure hypertensive cohorts. As the nondipping pattern is a derivative extract of both daytime and nightt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 100 publications
(65 reference statements)
5
43
1
1
Order By: Relevance
“…27 One recent study showed that the nondipping pattern of nocturnal blood pressure is more common in patients with RLS compared to controls, 28 which has been suggested to be an independent risk factor for cardiovascular events. 29 Positive associations between RLS and CVD had also been consistently observed in cross-sectional studies with ORs ranging from 1.4 to 2.9. 9 In one prospective study, a significantly higher risk of coronary heart diseases (HR 1.7; 95% CI 1.1-2.6) was found among people with RLS for .3 years relative to those without RLS.…”
Section: Methods Study Population the Hpfs Was Established Inmentioning
confidence: 91%
“…27 One recent study showed that the nondipping pattern of nocturnal blood pressure is more common in patients with RLS compared to controls, 28 which has been suggested to be an independent risk factor for cardiovascular events. 29 Positive associations between RLS and CVD had also been consistently observed in cross-sectional studies with ORs ranging from 1.4 to 2.9. 9 In one prospective study, a significantly higher risk of coronary heart diseases (HR 1.7; 95% CI 1.1-2.6) was found among people with RLS for .3 years relative to those without RLS.…”
Section: Methods Study Population the Hpfs Was Established Inmentioning
confidence: 91%
“…21 The prognosis of nocturnal hypertension in treated hypertensive patients was investigated in several studies 29,30 and summarized in a systematic narrative review. 31 These studies clearly demonstrated the importance of nocturnal hypertension in the management of hypertension. However, defining nocturnal hypertension in subjects with normal clinic blood pressure, especially the isolated form, has quite different clinical implications in the identification and management of hypertension.…”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 97%
“…26 Perez-Lloret et al 24 in a study including 233 untreated and treated hypertensives were able to demonstrate that nocturnal hypertension defined by fixed cutoff limits recommended by the 2007 European Society of Hypertension/European Society of Cardiology 27 was a better predictor of LVH (odds ratio, 11.1; 95% CI, 3.0-40.1; P<0.001) than the nondipping pattern (odds ratio, 1.4; 95% CI, 0.4-5.5; P=NS).…”
Section: Discussionmentioning
confidence: 99%